2018
DOI: 10.1177/1062860618808378
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Inpatient Venous Thromboembolism Prophylaxis: A Single Institution’s Concurrent Review

Abstract: Hospital-acquired venous thromboembolism (VTE) affects morbidity and mortality and increases health care costs. Poor adherence to recommended prophylaxis may be a potential cause of ongoing events. This study aims to identify institutional adherence rates and barriers to optimal VTE prophylaxis. The authors performed patient and nurse interviews and a concurrent review of clinical documentation, utilizing a cloud-based, HIPAA-compliant tool, on a convenience sample of hospitalized patients. Adherence and agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…A review stated that in-patients’ adherence to VTE treatments strongly depended on the nurse’s health education. 33 Gibbs et al. 34 concluded that nurses who are committed to VTE risk assessment and prophylaxis can greatly contribute to the reduction of VTE cases and the subsequent complications.…”
Section: Discussionmentioning
confidence: 99%
“…A review stated that in-patients’ adherence to VTE treatments strongly depended on the nurse’s health education. 33 Gibbs et al. 34 concluded that nurses who are committed to VTE risk assessment and prophylaxis can greatly contribute to the reduction of VTE cases and the subsequent complications.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses with positive attitude toward VTE prevention had higher awareness of the importance of self-education as well as education of patients on VTE prevention [34]. However, according to the present data, there were nearly 20% of nurses did not provide timely and necessary health education for patients, which may lead to increased risk of VTE and related morbidity and mortality [40,41]. Our ndings suggest that more education and support may be needed to improve nurses' knowledge and attitude toward VTE prevention, especially in the aspect of patient education.…”
Section: Discussionmentioning
confidence: 57%
“…Nurses with positive attitudes toward VTE prevention had higher awareness of the importance of self-education as well as patient education on VTE prevention ( Lee et al, 2014 ). However, according to the present data, nearly 20% of nurses did not provide timely and necessary health education for patients, which may lead to an increased risk of VTE and related morbidity and mortality ( Bauer et al, 2019 ; Lavall & Costello, 2015 ). Our findings suggest that more education and support may be needed to improve nurses’ knowledge and attitudes toward VTE prevention, especially in the aspect of patient education.…”
Section: Discussionmentioning
confidence: 64%